Writing Local Histories within Transnational Frameworks - Michelsen, Morten (Danish Yearbook of Musicology, 2007)
Using examples from rock museums, from the rock press, and from text books on the history of rock I establish that the rock ideology first articulated in the late 1960s is alive and well in the 21st century. One aspect of this ideology is the rather self-conscious relation to history writing which has resulted in a grand narrative based on traditional art music historiography complete with a canon of white, male, guitar-playing singer-songwriters. This narrative even seems to dominate history writing in other places than England and North America, in this case Denmark. Theories of transnational cultural flows – including their focus on centre–periphery relations – are suggested in order to analyse this domination and to articulate other narratives that do not mirror the structure of the Anglo-American narrative. The article closes with some remarks on the differences between rock ’n’ roll in Denmark and North America using the Danish musician Melvis’ recording of ‘Jailhouse Rock’ as an example.